1990
DOI: 10.1080/02724936.1990.11747411
|View full text |Cite
|
Sign up to set email alerts
|

Oral zinc supplementation in persistent diarrhoea in infants

Abstract: A controlled randomized trial was conducted in 40 infants (6-18 months old) with persistent diarrhoea (greater than 2 weeks' duration) to evaluate the effect of oral zinc supplementation. After completion of rehydration, 20 infants in group A received oral zinc sulphate (20 mg elemental zinc twice daily) and an equal number in group B were given a placebo (glucose). Each child was given oral nalidixic acid and a similar milk-free feeding schedule. Both the groups were comparable with respect to various initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 18 publications
3
33
3
Order By: Relevance
“…Several studies examined the therapeutic effects of zinc on persistent diarrhea. Again, the first study on this topic was conducted by Sachdev et al in India (16). This was a hospital-based inpatient study of children 6-18 mo of age (average age 9 mo).…”
Section: Therapeutic Effects Of Zinc On Diarrheamentioning
confidence: 99%
“…Several studies examined the therapeutic effects of zinc on persistent diarrhea. Again, the first study on this topic was conducted by Sachdev et al in India (16). This was a hospital-based inpatient study of children 6-18 mo of age (average age 9 mo).…”
Section: Therapeutic Effects Of Zinc On Diarrheamentioning
confidence: 99%
“…In conclusion, the addition of zinc directly to an ORS may operate in several possible ways: a) by providing a readily absorbable form of zinc to zinc-depleted tissues, where zinc may also act as an antiinflammatory agent (27)(28)(29)(31)(32)(33)(34)(35)(36); 2) by introducing antioxidant organometallic complexes (42,43,(45)(46)(47), capable of inducing MT synthesis in the enterocyte (48,49); or c) by scavenging NO diffusing out of the enterocyte, especially under conditions of increased NO synthesis, thus creating a NO gradient toward the intestinal lumen. …”
Section: Resultsmentioning
confidence: 99%
“…This connection was first inferred from reports of low plasma zinc in children with diarrhea (27,28). More recently, it has been shown that serum and rectal biopsy zinc concentrations are decreased in children and infants with chronic diarrhea (29). Also, considerable zinc losses have been reported in children with acute dehydrating diarrhea (30).…”
mentioning
confidence: 99%
“…Zinc supplementation has also been shown to have a therapeutic effect on diarrhea episodes, especially persistent diarrhea, in several hospital-based studies in which malnourished children or children with diarrhea had been admitted (18)(19)(20)(21)(22)(23)(24). The effect of zinc supplementation could depend on nutritional status, on age, and, of course, on zinc status at admission.…”
Section: Introductionmentioning
confidence: 99%